Estrategia de marketing digital en la Piladora "Mejía Coca" ubicado en la ciudad de Babahoyo, en el periodo 2023. - Fajardo Moreno, Betsy Mayerli (2024)
The objective of this project is to create digital marketing strategies in Piladora Mejia Coca in order to achieve a positive impact on the business and contribute to local economic development, since the rice sector both in the city of Babahoyo and nationally greatly affects the economy, being one of the main livelihood activities of many families in the region, and it becomes necessary to promote innovation in the marketing processes of this productive area. The problem in the case, revolves around the difficulties that the Piladora Mejia Coca has to attract and retain customers through digital media, as a result of the fact that, not having effective marketing, the work done for online promotion purposes does not guarantee results, and affect the commercial part. The methodology used in the development of the research considers the deductive method and the application of an interview with the owner of the establishment, which yielded information that was tabulated for better analysis. As a conclusion, it is indicated that the piladora has many shortcomings in its marketing procedures, therefore, it is advisable to opt for strategies that focus on disseminating trending contents that attract consumers and benefit the business trade.